Deep Ecology and Social Critique - Mackevičiūtė, Jūratė (Problemos, 2002)
The purpose of this paper is to discuss ethical responses to the ecological crisis and to present some suggestions how we could and must do better. Three kinds of environmental ethics are distinguished and surveyed: the shallow, the intermediate, and the deep one. Then some strategies for realising the eco centric ethic are discussed with special attention paid to idea of green citizenship.
Keywords: deep ecology; ecofeminism; anthropocentrism; ecocentrism